2018
DOI: 10.1080/25765299.2018.1449344
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of algal consumption as an alternative food in the Kingdom of Bahrain

Abstract: Algae are living organisms with high nutritional benefits. As such, algae are considered a solution to malnutrition and starvation. Individuals in the Gulf Corporation Council (GCC) region have limited food resources and face problems linked to malnutrition. Therefore, the introduction of a new food to their diet, such as algae, would be beneficial. However, these populations have conservative food habits and might not accept such anew food. Therefore, here we assessed consumer acceptance of natural and proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In addition, 71.5% of the population showed interest in or willingness to know more about these nutritionally rich seaweeds, and the enthusiasm for perceiving additional knowledge about their nutritional potential was reported to be equally spread between males (80.1%) and females (78.8%), which is in contrast to the study reported by Birch et al, (2018), wherein females (42%) reported a higher level of consumption of seaweeds compared to males (32%). These findings are in accordance with Al-Thawadi (2018) and Bührlen et al, (2005) regarding the higher acceptance of edible seaweeds by the public, which might be due to their proven nutritional benefits as well as their emerging role in the area of complementary and alternative medicines [ 29 , 30 , 31 ]. Furthermore, the major form of seaweed utilization was found in the form of snack items followed by soups, similar to the study of Birch et al, (2018).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, 71.5% of the population showed interest in or willingness to know more about these nutritionally rich seaweeds, and the enthusiasm for perceiving additional knowledge about their nutritional potential was reported to be equally spread between males (80.1%) and females (78.8%), which is in contrast to the study reported by Birch et al, (2018), wherein females (42%) reported a higher level of consumption of seaweeds compared to males (32%). These findings are in accordance with Al-Thawadi (2018) and Bührlen et al, (2005) regarding the higher acceptance of edible seaweeds by the public, which might be due to their proven nutritional benefits as well as their emerging role in the area of complementary and alternative medicines [ 29 , 30 , 31 ]. Furthermore, the major form of seaweed utilization was found in the form of snack items followed by soups, similar to the study of Birch et al, (2018).…”
Section: Discussionsupporting
confidence: 89%
“…Energy Environmental concern (þ), Perceived benefits (þ), Self-efficacy (þ), Cues to action (n.s), General concern (n.s), Perceived barriers (n.s), Perceived severity (n.s), Perceived susceptibility (n.s). Al-Thawadi (2018) 30 students for experiment þ 300 questionnaire, non-probability, Bahrain.…”
Section: Generic Sustainable Behaviormentioning
confidence: 99%
“…Familiarity and experience with innovative and novel foods enhances consumer acceptance [55,56] and are important drivers for these products. Attempts to introduce novel…”
Section: Discussionmentioning
confidence: 99%